The complete chloroplast genome sequence of Lycium barbarum var. implicatum (Solanaceae), a new species of wolfberry from the Yellow River Basin in Ningxia, China - Bo Zhang; Wangsuo Liu; Darifu Ba; Zhiguo Jiang (Mitochondrial DNA. Part B. Resources)
Lycium barbarum var. implicatum (2010), is a new variety of L. barbarum in Solanaceae. Here, we sequenced, assembled, and annotated the complete chloroplast (cp) genome of L. barbarum var. implicatum. Results showed that the complete cp genome of L. barbarum var. implicatum was 154,888 bp in length, containing a large single copy (LSC) region of 85,894 bp, a pair of inverted repeats (IR) region of 25,393 bp, and a small single copy (SSC) region of 18,208 bp. Maximum-likelihood (ML) phylogenetic tree elucidated that L. barbarum var. implicatum was sister to L. ruthenicum. Our results provide useful information for future phylogenetic studies in the family of Solanaceae.